MILITARY ADMINISTRATION OF ANCIENT AND MEDIEVAL INDIA- A CRITICAL ANALYSIS - Zumeer Ahmad Sofi (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2023)
So far as the military administration of any country is concern it always considered an integral and formidable part of any country. It not only reflects the might, defence but also measures the parameter of a country’s indomitable strength in present days India security force is of a great continuity of our past. It not only establishes the technique of managing the safety of India but also keep the enemy eyes far off. It plays an important role in managing the public affairs in a society as it works equivalent to public administrative guidance of our civil society. Military Administration have a wide scope and can be applied in civil, political, bureaucratic affairs as all these aspects are in-separable part of any society. It acts as a crucial step for the peace and prosperity of a country.